2017
DOI: 10.1002/rth2.12029
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics and pharmacodynamics of idarucizumab, a specific dabigatran reversal agent in healthy Japanese volunteers: a randomized study

Abstract: Essentials Idarucizumab, a monoclonal antibody fragment, binds dabigatran with high affinity and specificity.In this phase 1 trial, healthy Japanese males received idarucizumab alone or with dabigatran.Idarucizumab achieved immediate, complete and sustained reversal of dabigatran anticoagulation.Idarucizumab was well tolerated and demonstrated no pro‐coagulant effects. BackgroundIdarucizumab is a humanized monoclonal antibody fragment that specifically binds with high affinity to dabigatran.ObjectivesThis stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…As idarucizumab is specific to dabigatran, it does not promote or inhibit thrombosis [9,10]. Phase I studies in Caucasian and Japanese subjects [9,11,12] and the global phase III study (RE-VERSE AD) [13] showed that idarucizumab rapidly reverses the anticoagulant effect of dabigatran.…”
Section: Introductionmentioning
confidence: 99%
“…As idarucizumab is specific to dabigatran, it does not promote or inhibit thrombosis [9,10]. Phase I studies in Caucasian and Japanese subjects [9,11,12] and the global phase III study (RE-VERSE AD) [13] showed that idarucizumab rapidly reverses the anticoagulant effect of dabigatran.…”
Section: Introductionmentioning
confidence: 99%
“…A decreased immune response in the very elderly may account for this. The age of patients in this study (mean, 76.6 years; median, 78 years) was substantially higher compared with the volunteers in phase I (mean, 36 years; median, 32 years) . Overall, anti‐idarucizumab ADAs were detected in a small fraction (5.6%) of the investigated patient population.…”
Section: Discussionmentioning
confidence: 65%
“…Details on all utilized clinical studies and on their assignment to a test or training dataset are provided in Table 1 and Table S1 of the Electronic Supplementary Material (ESM). For the presented PBPK analysis, experimental data of five published clinical trials were available [14,[17][18][19][20][21][22][23], including healthy, elderly, and renally impaired Caucasian individuals, healthy Japanese individuals, and a diverse group of patients requiring dabigatran reversal. Idarucizumab was applied intravenously in doses between 20 mg and 8000 mg, either alone or in combination with orally applied, steady-state dabigatran (150 mg or 220 mg of dabigatran etexilate).…”
Section: Idarucizumab Physiologically Based Pharmacokinetic Modelmentioning
confidence: 99%
“…S8 and S9 of the ESM, illustrating the good prediction of the drastic reduction of dabigatran plasma concentrations by idarucizumab. [14,17]; e, f Caucasian individuals with mild renal impairment (RI), pre-treated with 150 mg of DE bid [14,17], and g, h healthy Japanese individuals [19,21].…”
Section: Idarucizumab-dabigatran Interactionmentioning
confidence: 99%
See 1 more Smart Citation